Anestesia troncular al nervio maxilar superior. Técnica de Carrea. Descripción de la técnica - Burbano Salazar, Manuel Alberto; Rios, Hector Fabio (Revista Estomatología, 1999)
It was realized a revision about different anesthetic solutions, their properties, their uses as well as advantages and disadvantages. It is described to the Superior Maxillary Nerve anesthethic tecnique using the posterior palatine forame as the access way, performing a conductive infiltration in to the Pterigopalatine fossa. Some indications and contraindications are proposed and some recommendations for their use are given.